An Improved Synthesis Phase Unwrapping Method Based on Three-Frequency Heterodyne - Jiangtao Liu; Peng Tian; Hongru Li; Hao Wei; Guoliang Deng; Shouhuan Zhou; Zeyu Ma; Wenwu Wang; Liang He (Sensors, 2022)
An improved three-frequency heterodyne synthesis phase unwrapping method is proposed to improve the measurement accuracy through phase difference and phase sum operations. This method can reduce the effect of noise and increase the equivalent phase frequency. According to the distribution found in the phase difference calculation process, the Otsu segmentation is introduced to judge the phase threshold. The equivalent frequency obtained from the phase sum is more than those of all projected fringe patterns. In addition, the appropriate period combinations are also studied. The simulations and related experiments demonstrate the feasibility of the proposed method and the ability to improve the accuracy of the measurement results further.